Consensus of Linear Multiagent Systems With Actuator Saturation and External Disturbances - Deng, Chao; Yang, Guang-Hong (IEEE transactions on circuits and systems. II, Express briefs, 2017)
This brief considers the leader-following consensus problem for linear multiagent systems with actuator saturation and external disturbances. By enlarging the contractively invariant set to estimate the domain of consensus attraction (DOCA) of the origin, this brief derives a condition to estimate the DOCA under the actuator saturation and magnitude-bounded disturbances. For the energy-bounded disturbance case, a sufficient condition is obtained under which trajectories starting from an ellipsoid will remain inside an outer ellipsoid. Moreover, all the optimization problems are transformed into the corresponding convex optimization algorithms with linear-matrix-inequality constraints. Finally, a simulation example is given to illustrate the effectiveness of the proposed control scheme.